Dark day in the deep sea - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2008)
Eight-year-old Jack and his seven-year-old sister, Annie, learn about the ocean, solve the mystery of its fabled sea monster, and gain compassion for their fellow creatures after joining a group of nineteenth-century explorers aboard the H.M.S. "Challenger."
"A Merlin mission."
"A Stepping Stone book."
3.8
3-6
Keywords: Oceanography -- Juvenile fiction; Challenger (Ship : 1872-1876) -- Juvenile fiction; Compassion -- Juvenile fiction; Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Tree houses -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Oceanography -- Fiction; Challenger (Ship : 1872-1876) -- Fiction; Compassion -- Fiction; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction; Brothers and sisters -- Fiction; Oceanography -- Fiction; Challenger (Ship : 1872-1876) -- Fiction; Compassion -- Fiction; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction; Siblings -- Fiction